Comparison of Different Molecular Weights of Intra-Articular Hyaluronic Acid Injections for Knee Osteoarthritis: A Level I Bayesian Network Meta-Analysis - Migliorini, Filippo; Maffulli, Nicola; Nijboer, Cornelis Hindriks; Pappalardo, Gaetano; Pasurka, Mario; Betsch, Marcel; Kubach, Joshua (Biomedicines, 2025)
Background: The present Bayesian network meta-analysis compared the efficacy of intra-articular injections of different molecular weights of hyaluronic acid (HA) in patients with knee osteoarthritis. Methods: In November 2024, the following databases were accessed: PubMed, Web of Science, Google Scholar, and Embase. All randomised controlled trials investigating the efficacy of intra-articular HA injections for knee osteoarthritis were accessed. The outcome of interest was to evaluate pain according to the visual analogue scale (VAS). The groups included for comparison were the ultra-high molecular weight (UHMW), high molecular weight (HMW), medium molecular weight (MMW), and low molecular weight (LMW). Results: Data from 9822 patients were collected. The mean age of the patients was 62.1 ± 5.0 years with given comparability at baseline. Different follow-up periods were compared. The longest control period ranged from four to six months, and the UHMW and HMW injections were the interventions associated with the greatest reduction in the VAS. LMW HA was the intervention associated with the lowest decrease in VAS, falling short of the control group. Conclusions: The main findings of the present Bayesian network meta-analysis, with a current level I of evidence, suggests that the UHMW and HMW HA has a beneficial effect on pain at 6 months post intervention in patients with knee osteoarthritis.
CRIS-Team Scopus Importer:2025-01-31
Keywords: hyaluronic acid; injections; knee; osteoarthritis